2006
DOI: 10.1111/j.1468-3156.2005.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of a new integrated mental health service for people with learning disabilities

Abstract: Accessible summary• People with learning disabilities can have mental health problems like anyone else.• People with learning disabilities should be able to use the same mental health services as anyone else. • In this article we say how we have tried to make this happen. SummaryIt is now well recognized that people with learning disabilities experience the full range of psychiatric disorders. Public policy in the United Kingdom advocates that people with learning disabilities should access mainstream mental h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…Carers reported some positive aspects of this experience; however, the overall conclusion was that services were seen as lacking flexibility in meeting the needs of people with intellectual disabilities. A number of models have been reported including services that provide specialist care for people with intellectual disabilities and mental ill health (e.g., Hackerman, Schmidt, Dyson, Hovermale, & Gallucci, ) and those that provide integrated care (e.g., Hall, Higgins et al, ; Hall, Parkes et al, ). There is still not sufficient evaluation of such service structures to be confident about the approach that will work best for people with intellectual disabilities, although studies suggest that distinguishing between the activities of specialist mental health services and well‐functioning multi‐disciplinary intellectual disability teams may be difficult (e.g., Martin et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carers reported some positive aspects of this experience; however, the overall conclusion was that services were seen as lacking flexibility in meeting the needs of people with intellectual disabilities. A number of models have been reported including services that provide specialist care for people with intellectual disabilities and mental ill health (e.g., Hackerman, Schmidt, Dyson, Hovermale, & Gallucci, ) and those that provide integrated care (e.g., Hall, Higgins et al, ; Hall, Parkes et al, ). There is still not sufficient evaluation of such service structures to be confident about the approach that will work best for people with intellectual disabilities, although studies suggest that distinguishing between the activities of specialist mental health services and well‐functioning multi‐disciplinary intellectual disability teams may be difficult (e.g., Martin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…There is an increased emphasis on people with intellectual disabilities using mainstream services; however, some authors have suggested that integrated services may not fully meet the needs of people with lower abilities (e.g., Chaplin et al, 2006). For example, Hall, Higgins et al (2006) reported the experiences of people with intellectual disabilities in mainstream community and inpatient mental health services. They reported that people with intellectual disabilities in mainstream inpatient services had more unmet needs and were at greater risk compared with those in community settings.…”
Section: Introductionmentioning
confidence: 99%
“…The model we eventually decided upon involved the identification of four beds for people with learning disabilities within a mainstream, 16‐bedded inner‐city psychiatric ward (Hall et al. 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The model we eventually decided upon involved the identification of four beds for people with learning disabilities within a mainstream, 16-bedded inner-city psychiatric ward (Hall et al 2006). Additional staff were deployed to provide in-reach support to this service and additional systems were developed to support appropriate admissions, discharges and longer-term follow up.…”
Section: Introductionmentioning
confidence: 99%
“…Hall et al . (2006a) described the development in London of a new integrated service for people with ID.…”
Section: Resultsmentioning
confidence: 99%